2018
DOI: 10.1177/0844562117747191
|View full text |Cite
|
Sign up to set email alerts
|

Youth Homelessness: The Impact of Supportive Relationships on Recovery

Abstract: AIM:To test a model based on Peplau's theory of Interpersonal Relations, which examines the influence of a network of service providers, perceptions of social supports and perceptions of family relations on a homeless youth's perceptions of recovery. BACKGROUND:Homeless youth comprise an extremely disenfranchised group and have been recognized as one of the fastest growing sub-groups within the homeless population. Homeless youth face impaired access to health and social services. They are often left unsupport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
2
4
0
1
Order By: Relevance
“…This result is consistent with Peplau's Theory of Interpersonal Relations [30,31] that highlights the importance of supportive relationships in achieving health. This result is also consistent with some previous studies [46], which found that family relations were significant predictors in mental health perceptions of the recovery process of homeless youth. Although homeless people have sometimes volatile relationships with family members, these results confirm that family relationships are important for health [33,34].…”
Section: Interpersonal Relationships and Srhsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with Peplau's Theory of Interpersonal Relations [30,31] that highlights the importance of supportive relationships in achieving health. This result is also consistent with some previous studies [46], which found that family relations were significant predictors in mental health perceptions of the recovery process of homeless youth. Although homeless people have sometimes volatile relationships with family members, these results confirm that family relationships are important for health [33,34].…”
Section: Interpersonal Relationships and Srhsupporting
confidence: 93%
“…Also, people who perceive higher levels of support from social services have a better perception of their health. These results are consistent with the finding of social support related to higher levels of health and social service utilization among homeless persons in other studies [42,46]. In a recent systematic review of homeless persons' experiences of health-and social care, being cared for and respected in the professional relationship were described as supportive, while experiences of alienation, discrimination, disrespect, and stigmatisation were experienced as unhelpful [62].…”
Section: Social Services Support and Srhsupporting
confidence: 89%
See 1 more Smart Citation
“…Raziskava je potekala leta 2015 med mladimi brezdomci in je kot teoretični okvir uporabila teorijo medosebnih odnosov. Ugotovili so, da močnejša socialna podpora in boljši odnosi z družino lahko prispevajo k boljšemu zaznavanju okrevanja mladih brezdomcev (Gasior, 2015). Teorija medosebnih odnosov predstavlja ustrezno teoretično podporo tudi pri odnosu med medicinsko sestro in pacientom v primeru, ko so pacienti žrtve spolnega nasilja, kar zahteva veliko podpore, razumevanja in zaupanja (Courey, et al, 2008).…”
Section: Možnost Testiranjaunclassified
“…Furthermore, a lack of social connectedness among the homeless, including repeated social exclusion, social isolation [ 22 , 23 ], and low levels of social support and social functioning, have been shown to contribute to poor health [ 23 ]. Relationships with family have also been shown to be significant predictors of lower self-reported health status among those experiencing homelessness [ 24 ], and one study found family support to be a key contributor to positive views of recovery from mental health illness among homeless youth [ 25 ].…”
Section: Introductionmentioning
confidence: 99%